Photocatalytic oxidation of phenol, cyclohexanol and hexanol by titania dispersed on mesoporous silica MCM-41 - Mohd. Nor, Nur Umisyuhada (2015)
Alcohol is a useful compound, but the excessive exposure of alcohol is hazardous to human and must be treated. Therefore, photocatalysis has been proposed to be an alternative method to oxidize the alcohol and titanium dioxide (TiO2) has been recognized as the most potential photocatalyst. In this study, in order to increase the efficiency of TiO2, TiO2-MCM-41 series were prepared by an impregnation method. The X-ray diffraction patterns and nitrogen adsorptiondesorption analysis revealed the successful formation of MCM-41. The X-ray diffraction patterns also showed that the pure phase of TiO2 is anatase. The structure of MCM-41 was maintained when the loading amount of TiO2 was low (up to 5 wt%). The successful formation of TiO2-MCM-41 was also confirmed by fluorescence spectroscopy. On the other hand, diffuse reflectance ultraviolet visible spectrum showed that the sample with 5 wt% of TiO2 (TiO2(5)-MCM-41) loading has the most dispersed TiO2 among the TiO2-MCM-41 samples. The good dispersion of TiO2 on the MCM-41 was also observed by field emission scanning electron microscopy and the energy dispersive X-ray mapping analyses. The TiO2-MCM-41 with 5 wt% of TiO2 loading showed the highest turnover number (TON) which is 0.27 for phenol oxidation. The dispersion of TiO2 and well maintained MCM-41 structure were proposed to be the important parameters for the high activity of the photocatalyst. The kinetic study revealed that phenol oxidation followed first order with the rate constant of 0.33 h-1, while the study on the mechanism of reaction proposed that the positive holes acted as the active sites in phenol oxidation. The activity of the best photocatalyst, TiO2(5)-MCM-41 was also tested for oxidations of cyclohexanol and hexanol. The photocatalytic activity increased in the order of hexanol < cyclohexanol < phenol. It is suggested that the strongest interaction and adsorption between phenol and the photocatalyst led to the highest activity. In contrast, cyclohexanol oxidation followed second order with the rate constant of 0.026 M-1 h-1 while, the hexanol oxidation followed pseudo-first order with the rate constant of 0.014 h-1. Scavenger tests results proposed that the superoxide radicals acted as the active species for both cyclohexanol and hexanol oxidations.